2004
DOI: 10.1002/ejic.200400309
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Generation of Lanthanide(II) Halides in THF and Simple Quantitative Determination

Abstract: Lanthanide(II) reagents (SmI2, SmBr2, YbI2, EuI2) have been prepared rapidly in high yields using microwave‐assisted heating. Samarium diiodide is obtained as a saturated solution in THF (0.13 M) within 5 min and ytterbium diiodide (0.065 M) after 45 min. A simple method for quantitative determination of LnX2 in THF is also described by utilizing the instantaneous reaction with ketones in the presence of an amine and water. This method establishes the concentration of the active single‐electron‐donor species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
1
33
0
1
Order By: Relevance
“…The concentration of SmI 2 was determined by iodometric titration or by the method developed by Hilmersson. [17] Benzyl bromide, dg, dgme, and dgde were dried over activated molecular sieves. Dried solvents and reagents were stored in an Innovative Technology, Inc. drybox containing an argon atmosphere and a platinum catalyst for drying.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of SmI 2 was determined by iodometric titration or by the method developed by Hilmersson. [17] Benzyl bromide, dg, dgme, and dgde were dried over activated molecular sieves. Dried solvents and reagents were stored in an Innovative Technology, Inc. drybox containing an argon atmosphere and a platinum catalyst for drying.…”
Section: Methodsmentioning
confidence: 99%
“…(5)]. [13] However, perhaps the most convenient method of synthesis of SmBr 2 was reported by Flowers and coworkers who utilized readily available SmI 2 and LiBr [Scheme 2, Eq. (1)].…”
Section: Samarium(ii) Bromidementioning
confidence: 99%
“…[97] On the basis of kinetic studies, the mechanism involving two SETs from europium(II) has been proposed. Perhaps the most intriguing aspect of this work is that nicotinic and picolinic acids [97b] as well as dialkylketones [13] were shown to be unreactive towards europium(II), thus showing the potential for chemoselective reductions. Furthermore, it is worth noting that both YbI 2 and EuI 2 provide important entry points to organometallic complexes of ytterbium and europium with downstream applications in inorganic chemistry, catalysis and polymerization.…”
Section: Other Lanthanide(ii) Reagentsmentioning
confidence: 99%
“…Altogether this makes these reactions less attractive with respect to large-scale syntheses. Previously, we have reported that SmI 2 and particularly SmBr 2 can be generated as suspensions in THF, [6] thus requiring a smaller volume of THF. The use of smaller volumes of solvent in reduction reactions is important as it allows reduction reactions to be carried out on a larger scale in smaller reaction vessels.…”
Section: Full Papermentioning
confidence: 99%